2019
DOI: 10.2196/10530
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Radiation Oncologists’ Awareness of Online Reputation Management

Abstract: Background Online reputation management (ORM) is an emerging practice strategy that emphasizes the systematic and proactive monitoring of online reviews relating to one’s professional reputation. Objective We developed this survey project to assess whether radiation oncologists are aware of ORM and how it is utilized in their practices. We hypothesized that ORM is largely unknown by most practicing radiation oncologists and that little time is spent actively managing th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Experience related to online reputation management suggests that a single negative review likely has a greater influence than multiple positive evaluations [19]. Despite this fact, a large percentage of physicians do not check their online profile [8,20]. Physician criticism of PRWs is understandable given previous studies demonstrating inconsistencies between patient ratings and quality of care [21-25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experience related to online reputation management suggests that a single negative review likely has a greater influence than multiple positive evaluations [19]. Despite this fact, a large percentage of physicians do not check their online profile [8,20]. Physician criticism of PRWs is understandable given previous studies demonstrating inconsistencies between patient ratings and quality of care [21-25].…”
Section: Discussionmentioning
confidence: 99%
“…Suggested approaches involve the use of collateral to solicit reviews, including patient cards, videos, and emails [9]. In addition, patients can be encouraged to complete online ratings and surveys at the time of encounter, thus offering a more proactive approach [8]. Finally, appropriately addressing negative comments or providing personalized review responses is suggested as a potential method of demonstrating physician focus on the patient experience to other potential patients visiting the PRW [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, satisfaction with practice personnel correlates with higher physician ratings ( 7 ). As such, authors have suggested active steps that can be taken to optimize these interpersonal variables and manage online digital reputation, such as personalized emails and other online content ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%